Efficacy of Tai Chi-Style Multi-Component Exercise on Frontal-Related Cognition and Physical Health in Elderly With Amnestic Mild Cognitive Impairment - Yang, Shao-Yun; Lee, Hsuei-Chen; Huang, Chih-Mao; Chen, Jin-Jong (Frontiers in Aging, 2021)
Early prevention from accelerated neurocognitive declines with advanced aging and the delay of the onset of dementia have became paramount for the achievement of active aging. The present study examined whether the proposed non-pharmaceutical, multi-component exercise training which combined Tai-Chi exercise, Aerobic fitness, and thera-band therapy protects against age-related neurocognitive and physical deterioration in the older participants with amnestic mild cognitive impairment (aMCI). Participants with aMCI in the quasi-experimental design were assigned to the multi-component exercise group or care control group. Evaluations of neuropsychological function and functional fitness were performed before and after 12-weeks intervention, and after 24-weeks follow-up. Our results showed that the multi-component intervention significantly improved various domains of neurocognitive function, particularly in memory- and frontal-related cognition, and better performance on functional fitness, including muscle strength, cardiopulmonary endurance, and agility. Furthermore, such beneficial effects were preserved after 24 weeks. The findings provide supportive evidence that non-pharmaceutically multi-component intervention with Tai-Chi style practice as a core exercise may protect against age-related neurocognitive and physical deficits and lay the path on developing age-friendly intervention programs to delay, or even reverse, the progression of MCI to dementia.